Diet and behaviour of young American Coots - Driver, E A (Wildfowl, 1988)
Young Coots became herbivorous with age and their dependence on adults for food declined as they grew. Adult involvement changed from providing food and shelter to merely providing a secure area for the young to forage. Young Coots less than 30 days old ate 84% animal matter; by 60 days of age the amount had declined to 21%. When 30-59 days old, they spent 53% (332 kJ day^-1) of their time feeding of which 5.5% was spent begging food from adults. This compared to 30% (81 kJ day^-1) for young Coots <30 days old who spent 44% of their foraging time begging. The dominant animal food item was insects. The average energy cost for daily activities of the three age classes calculated from time-budget studies ranged from 270 to 870 kJ day^-1. By the time the young were 60 days old (Class C) their feeding and other behavioural activities were very similar to adult birds.